Pengaruh Inflasi BI Rate dan Nilai Tukar Terhadap Harga Saham Perusahaan Sub Sektor Property dan Real Estate Periode 2022-2024 - Lani Ariani; Rispantyo Rispantyo (Pusat Riset dan Inovasi Nasional, 2026)
This study was conducted to examine the significance of the effects of inflation, the BI Rate, and the exchange rate on stock prices of property and real estate sub-sector companies listed on the Bursa Efek Indonesia during the 2022–2024 period. The population consisted of 92 companies, and a purposive sampling technique was used to obtain 9 sample companies. The research employed a descriptive quantitative approach using panel data regression analysis with EViews 13 software. Secondary data, including stock closing prices, inflation, the BI Rate, and the Rupiah exchange rate, were obtained from the official websites of the Indonesia Stock Exchange, Bank Indonesia, and the Kementerian Perdagangan. The results indicate that changes in inflation and exchange rates do not have a significant effect on stock prices. In contrast, changes in BI Rate volatility have a negative and significant effect on stock prices. This suggests that the BI Rate is the dominant factor considered by investors in the property sector compared to other variables. As an implication, investors are advised to prioritize BI Rate analysis when making investment decisions, while property companies need to strengthen interest rate risk mitigation strategies to maintain the stability of stock prices traded in the capital market